2004
DOI: 10.1196/annals.1330.018
|View full text |Cite
|
Sign up to set email alerts
|

Role of Alcohol Consumption in Escalation to Violence

Abstract: No other drug has been associated with aggressive and violent behavior more than alcohol has. A major characteristic of the link between alcohol and social interactions is the very large variation in who becomes more aggressive while drinking and who does not. Tracing the origins of these individual differences has led to a focus on predispositions, such as the antisocial behavior of Type 2 alcoholics. Successful development of an experimental procedure to model heightened aggressive behavior after voluntary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 71 publications
1
40
1
3
Order By: Relevance
“…These results suggest that CRF-R1 in areas other than the DRN probably modulate species-typical levels of aggressive behavior, whereas DRN CRF-R1 are particularly important when aggression is performed under the influence of alcohol. In all but one of the several experiments of this study (MTIP systemic CRF-R1 and 5-HT on alcohol-heightened aggression IM Quadros et al experiment), alcohol-heightened aggression was significantly observed in the overall group of animals, despite the known individual differences in this phenomenon (see Miczek et al, 2004). Such differences may have contributed to the absence of alcohol-escalated aggression in that particular cohort of mice.…”
Section: Blockade Of Crf-r1: Systemic Vs Drn Effects On Alcohol-relatmentioning
confidence: 55%
See 1 more Smart Citation
“…These results suggest that CRF-R1 in areas other than the DRN probably modulate species-typical levels of aggressive behavior, whereas DRN CRF-R1 are particularly important when aggression is performed under the influence of alcohol. In all but one of the several experiments of this study (MTIP systemic CRF-R1 and 5-HT on alcohol-heightened aggression IM Quadros et al experiment), alcohol-heightened aggression was significantly observed in the overall group of animals, despite the known individual differences in this phenomenon (see Miczek et al, 2004). Such differences may have contributed to the absence of alcohol-escalated aggression in that particular cohort of mice.…”
Section: Blockade Of Crf-r1: Systemic Vs Drn Effects On Alcohol-relatmentioning
confidence: 55%
“…Evidence for alcohol as a promoter of escalated levels of aggressive behavior has been established in laboratory settings, particularly in susceptible subgroups of individuals (Cloninger, 1987;Miczek et al, 2004). In mice, low to moderate doses of alcohol can escalate aggressive behaviors to levels that are significantly higher and more injurious than species-typical aggression (Miczek et al, 1998;Miczek and de Almeida, 2001), modeling critical features of alcoholescalated aggression.…”
Section: Introductionmentioning
confidence: 99%
“…For example, individuals who prefer the night hours have more opportunities to engage in ASB. Activities such as consuming alcohol may be more likely in ' eveningtypes ' and alcohol consumption is an activity that is known to predispose to ASB (Miczek et al 2004).…”
Section: Sibling Interactionmentioning
confidence: 99%
“…Importantly, in certain situations, Alc has the ability to facilitate aggressive actions. It has been repeatedly demonstrated, in multiple species, that some individuals are sensitive to the aggression-heightening effects of moderate doses of Alc, while most are not (Chance et al, 1973;Peeke et al, 1973;Miczek and O'Donnell, 1980;Lister and Hilakivi, 1988;Miczek et al, 1993Miczek et al, , 2004b. Although the neurobiological basis for the differential response to Alc is not yet known, there is compelling evidence for a significant role of the serotonin (5-HT) system in the modulation of impulsive aggressive behavior (Olivier et al, 1989;Olivier and Mos, 1992;Miczek et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%